(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This paper explores the significance of English for Specific Purposes (ESP) in engineering education. As the global demand for English-speaking professionals in technical fields grows, ESP emerges as a vital component of academic programs in engineering institutions. The study highlights how ESP bridges the gap between general language skills and technical communication needs, focusing on field-specific vocabulary, professional writing, and effective oral communication.